If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-13d + -18) + 20 = -18 + -17 + 19d Reorder the terms: -2(-18 + -13d) + 20 = -18 + -17 + 19d (-18 * -2 + -13d * -2) + 20 = -18 + -17 + 19d (36 + 26d) + 20 = -18 + -17 + 19d Reorder the terms: 36 + 20 + 26d = -18 + -17 + 19d Combine like terms: 36 + 20 = 56 56 + 26d = -18 + -17 + 19d Combine like terms: -18 + -17 = -35 56 + 26d = -35 + 19d Solving 56 + 26d = -35 + 19d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-19d' to each side of the equation. 56 + 26d + -19d = -35 + 19d + -19d Combine like terms: 26d + -19d = 7d 56 + 7d = -35 + 19d + -19d Combine like terms: 19d + -19d = 0 56 + 7d = -35 + 0 56 + 7d = -35 Add '-56' to each side of the equation. 56 + -56 + 7d = -35 + -56 Combine like terms: 56 + -56 = 0 0 + 7d = -35 + -56 7d = -35 + -56 Combine like terms: -35 + -56 = -91 7d = -91 Divide each side by '7'. d = -13 Simplifying d = -13
| 8(1-6x)+2=346 | | 4x+10+3x+6=180 | | 135/105 | | 81/(-9) | | -4-3n+3=23 | | x=218+508 | | 3.6/y=10.8/12 | | 30.99-25= | | 5(8x-8)=440 | | 11-8x=1-6x | | 3(5y-4)+15=5(y-3)-(3y+2) | | 12+3x=24-3x | | -20m+20=-17m-13 | | 20=12x+3 | | 5/6=x/6 | | 9x+(-7)=8x | | 10c=-11-3(-3c+1) | | -8r=-3r+20 | | x/6=0,5 | | 14v-12+7w+(-4v)= | | 20-y+20=2y-20 | | 6-0.5x=15 | | 9x+(17)=8x | | 8h+8=4h | | 18.75=3u | | 459.90=210x+1.19x | | 4=29+13x | | 6c=-8+2c | | -16-6-2g=-4(-g-20) | | y+3y-1=y | | -3g+4=9-8g | | 7x-x-10=-4 |